COMPLEX SENTENCES OF THE FRENCH AND UZBEK LANGUAGES AND THEIR FEATURES (Scientific journal of the Fergana State University, 2023)
The article provides an analytical overview of the construction of complex sentences in the French and Uzbek languages.